2012
DOI: 10.1016/j.jip.2012.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The scope of the crustacean immune system for disease control

Abstract: The culture or wild capture of marine and freshwater shellfish, including crustaceans, is without doubt a key source of protein for a burgeoning world population. Historically the expansion of aquaculture has, however, been accompanied by the increased incidence of economically significant diseases, most notably of viral and bacterial origin. Since the late 1970s great progress has been made in our understanding of the generalized protostome innate immune system. Distinct pathways, pathogen receptor proteins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(60 citation statements)
references
References 126 publications
0
57
0
3
Order By: Relevance
“…However, he also states that these approaches are considered somewhat crude and likely impose a net energetic cost to the host (see also Smith et al, 2003;Christensen et al, 2005;Hauton et al, 2007). Hauton (2012) therefore states that in an aquaculture setting, '(that this)...-blunt approach cannot serve as a global solution to the problems of commercially significant diseases'. As such, effective disease therapies can only be developed through a detailed understanding of the molecular pathways involved in immune surveillance within these hosts.…”
Section: Harnessing the Natural Disease Mitigation Strategies Of Crusmentioning
confidence: 99%
See 1 more Smart Citation
“…However, he also states that these approaches are considered somewhat crude and likely impose a net energetic cost to the host (see also Smith et al, 2003;Christensen et al, 2005;Hauton et al, 2007). Hauton (2012) therefore states that in an aquaculture setting, '(that this)...-blunt approach cannot serve as a global solution to the problems of commercially significant diseases'. As such, effective disease therapies can only be developed through a detailed understanding of the molecular pathways involved in immune surveillance within these hosts.…”
Section: Harnessing the Natural Disease Mitigation Strategies Of Crusmentioning
confidence: 99%
“…In this respect, observations of pathogen handling in wild populations may be utilised to identify markers of immune performance that could have direct relevance for application to farming situations. Hauton (2012) Specifically for the latter example, in their paper, Bartholomay et al (2012) have demonstrated that augmentation of the RNA interference (RNAi) response in shrimp to suppress virus infection and associated disease is a promising, emerging approach to shrimp virus disease control. Here, short fragments of RNA recog-nise and bind complimentary dsRNA sequences, thereby preventing specific gene expression (e.g.…”
Section: Harnessing the Natural Disease Mitigation Strategies Of Crusmentioning
confidence: 99%
“…The high concentration of granular cells in the haemolymph is related to the high phenoloxidase activity and resistance to disease. Granular cells have a role in phagocytosis, encapsulation, early recognition, melanisation and coagulation in some groups, producing and secreting antimicrobial peptides, and are involved in the cytotoxic reaction (Hauton, 2012).…”
Section: Immune Responsementioning
confidence: 99%
“…For example, infections with V. harveyi are known to cause extensive pathology and tissue inflammation in the gut and hepatopancreas of shrimps . Encapsulated pathogens are cleared from the circulation, and are often collected in the gills or hepatopancreas (Hauton, 2012). In this study, the EsHSC70-5 mRNA transcript was significantly upregulated in the heart and hepatopancreas as early as 12 h after challenge by V. parahaemolyticus, while the expression of EsHSC70-5 was significantly downregulated in the intestine and gills at nearly all time points compared to the controls.…”
Section: Discussionmentioning
confidence: 56%